CONSUMER CREDIT SCHEME OF PRIVATE COMMERCIAL BANKS: CONSUMERS’ PREFERENCE AND FEEDBACK - Rania Kabir; Ummul Wara Adrita (International Journal of Management Studies (IJMS), 2021)
In this article, the study is about the “Consumer credit scheme of banks in Bangladesh: consumers’ preference and feedback”. Four hypothesis have been developed to identify the potential customer group who contribute maximum in CCS program, to identify customer preference or more demandable product under Consumer Credit Scheme, to identify whether the services offered by the bank are convenient or not and finally to show how the customers view interest rate charged by the bank. For the study two sample private commercial banks have been chosen. Main focus of the study is given on the outcome that revealed from the hypothesis testing. The study also provides valuable recommendations as to remove those problems. Finally, the study also highlights a comparative analysis of CCS program of two sample banks.